Children’s music education: methods and forms (Eurasian Journal of Learning and Academic Teaching, 2022)
The problem of methods and organizational forms of education is considered sufficiently developed in pedagogy. Meanwhile, it is one of the most important problems of the theory and methodology of organizing the education of pupils and students youth. The article reveals the features of the methods and forms of organization musical education. The author conducts a historical and pedagogical analysis existing approaches to the classification of methods and forms of education, and on its basis develops the author's classification, taking into account the specifics of the language education